LEGAL MEASURES AGAINST FINANCIAL FRAUD: LEGISLATION AND PRACTICE ANALYSIS OF THE REPUBLIC OF KAZAKHSTAN (Journal of actual problems of jurisprudence, 2025)
The development of digital technology and digitalization has led to an increase in financial fraud, namely Internet fraud and telephone fraud. The aim of this article is to analyze the legislative framework of the Republic of Kazakhstan designed to combat financial fraud and to propose improvements for enhancing the relevant laws. The analysis of the current state and legal norms to combat financial pyramids, Internet fraud and telephone fraud helps to deepen theoretical knowledge in the field of law and allows developing countermeasures. The results of the study are of practical importance, as they can be used to improve existing laws and increase the effectiveness of the fight against financial fraud. The methodology of the study includes a literature review of sources, covering the analysis of scientific articles, statistical data, reports, as well as legislative and regulatory acts related to the prevention of financial fraud (in particular, financial pyramids, Internet and telephone fraud) in the Republic of Kazakhstan. The review and analysis of the study have indicated that the current regulatory framework requires revision to more effectively combat fraud. The findings emphasize the need to implement the proposed recommendations aimed at improving the legislation, which will reduce the scale of this phenomenon and reduce its negative consequences for society.Key words: Combating financial fraud, financial pyramids, Internet and telephone fraud